The extent to which multiple intelligences are available among grade eleven in governate of North Albatinah in Sultanate of Oman and its relationship with some variables = مدى توافر الذكاءات المتعددة لدى طلبة الصف الحادي عشر بمحافظة شمال الباطنة في سلطنة عمان وعلاقتها ببعض المتغيرات - Abdullah Mohammed Al-Mazruii, Abdul Aziz; Abu Kassim, Noor Lide; Saif Al-Mehrzi, Rashid (International Organization Center of Academic Research (OCERINT), 2020)
This quantitative study discusses the most available intelligence among eleventh grade students in North Al Batinah Governorate in the Sultanate of Oman. The problem is that the Career Guidance Center, which aims to help students in identifying their preferences and intelligence, uses the inclinations measures only, therefore, this study aims to identify the students' intelligence. The research adopted the descriptive and analytical method, a random sample consisted of (700) students was chosen. The study adopted (Shearer, 2004) Multiple Intelligence Scale, which consists of (119) phrases distributed in eight sub-scales: musical, physical, motor, logical, mathematical, spatial, verbal, linguistic, social, subjective and natural. The data were analyzed according to the descriptive analysis, to calculate the frequencies and percentages to determine the most available intelligence, the Kay square to find out the significance of the differences between the frequencies, and Spearman correlation coefficient for the extent of compatibility between the grades according to the variables of specialization and gender, and calculate the Pearson correlation coefficient. The findings revealed that: the most available intelligence among the members of the sample are: the subjective and social intelligence, while musical intelligence came in the last place. There are also statistically significant differences in logical mathematical intelligence in favor of males, and there are statistically significant differences in verbal linguistic intelligence in favor of females. There are positive and significant correlations between academic achievement and five intelligences: mathematical, spatial, verbal, social, and subjective logical. ******************************************************************************* تناقش هذه الدراسة الكمية أكثر الذكاءات توافراً لدى طلبة الصف الحادي عشر بمحافظة شمال الباطنة في سلطنة عمان. تكمن المشكلة أن مركز التوجيه المهني الذي يهدف إلى مساعدة الطلاب في التعرف على ميولهم وذكاءهم، لكنه يستخدم مقاييس الميول فقط، لذا فإن هذه الدراسة تهدف التعرف على الذكاء لدى الطلبة. اعتمد البحث المنهج الوصفي التحليلي، وتم اختيار عينة عشوائية تألفت عينة الدراسة من (700) طالبٍ وطالبة. اعتمدت الدراسة مقياس الذكاء المتعدد لـ (Shearer, 2004 ) المكون من (119) عبارة موزعة في ثمانية مقاييس فرعية هي: الموسيقي، والجسمي الحركي، والمنطقي الرياضي، والمكاني، واللفظي اللغوي، والاجتماعي، والذاتي، والطبيعي. تم تحليل البيانات حسب التحليل الوصفي، لحساب التكرارات والنسب المئوية لتحديد أكثر الذكاءات توافراً، وحساب مربع كاي لمعرفة دلالة الفروق بين التكرارات، وحساب معامل ارتباط سبيرمان لمدى التوافق بين الرتب تبعا لمتغيري التخصص والنوع، وحساب معامل ارتباط بيرسون. بينت النتائج أن أكثر الذكاءات توافراً بين أفراد العينة هما: الذكاءان الذاتي والاجتماعي، بينما جاء الذكاء الموسيقي في المرتبة الأخيرة. كما أنه توجد فروق ذات دلالة إحصائية في الذكاء المنطقي الرياضي لصالح الذكور، كما توجد فروق ذات دلالة إحصائية في الذكاء اللغوي اللفظي لصالح الإناث. ووجود فروق ذات دلالة إحصائية في الذكاء اللغوي اللفظي تعزى لمتغير التخصص لصالح تخصص العلوم الإنسانية، وتوجد فروق ذات دلالة إحصائية في الذكاء الطبيعي تعزى لمتغير التخصص لصالح العلوم الطبيعية. وجود ارتباطات موجبة ودالة بين التحصيل الدراسي وخمسة ذكاءات هي: المنطقي الرياضي، والمكاني، واللغوي اللفظي، والاجتماعي، والذاتي.